Stemming the Tide of Obstetric Morbidity: An Opportunity for the Anesthesiologist to Embrace the Role of Peridelivery Physician. Issue 3 (September 2016) - Mhyre, J.M.; Bateman, B.T.
Abstract : ( Anesthesiology. 2015;123(5):986–989) Today, the use of anesthesia and analgesia during childbirth accounts for 75% fewer maternal deaths than in 1980. Anesthesia-related complications such as high neuraxial block and difficult intubation still occur in roughly 1 of 3000 deliveries, although these complications are rare enough that there are not many population-level studies available. A recent study by Guglielminotti et al1 took on this subject by analyzing New York state administrative data from 2003 to 2012. The authors found that anesthesia-related complications had declined by 25% during this time period, with a 25% decrease in the risk of negative outcomes when using neuraxial anesthesia.